(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this work, we use the notion of the g μ-paracompact space ADeb to introduce two types of g μ-paracompact sets called α-g μ-paracompact and β-g μ-paracompact. We show that every α-g μ-paracompact set is β-g μ-paracompact and if a generalized topological space (S,μ) is g μ-paracompact, then every μ-closed subset in (S,μ) is α-g μ-paracompact while every μ g-closed subset in (S, μ) is β-g μ-paracompact. Finally, we introduce the notion of co-α-gμ-paracompact set as an application of α-gμ-paracompact and study some of its features.